Book review: Widén, Gunilla and Teixeira, José (eds.). Information literacy and the digitalisation of the workplace - Elena Maceviciute (Information Research: An International Electronic Journal)
Widén, Gunilla and Teixeira, José (eds.). Information literacy and the digitalisation of the workplace. London: Facet Publishing, 2023. xxviii, 166 p. ISBN 978-1-78330-579-7